Kolaborasi Bhabinkamtibmas dan Lembaga Adat Desa Dalam Upaya Mediasi Tindak Pidana Kekerasan Anak di Desa Karamabura Dompu - Ady Soepriadin; Ihlas Ihlas; Ilham Ilham; Hikmah Hikmah (SANGAJI: Jurnal Pemikiran Syariah dan Hukum, 2025)
This study aims to analyze the form of collaboration between Bhabinkamtibmas and village customary institutions in mediation efforts against criminal acts of violence against children in Karamabura Village, Dompu Regency. The problem of violence against children that is still rampant at the village level requires a solution approach that does not only rely on formal legal mechanisms, but also considers local wisdom values ??through customary institutions. This study uses a sociological juridical legal research method, namely an approach that examines law not only as a written norm (law in books), but also as a social reality that lives and develops in society (law in action). Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation, involving key informants from Bhabinkamtibmas elements, customary leaders, village officials, and the local community. The results of the study indicate that the form of collaboration that was built was synergistic, where Bhabinkamtibmas acted as a facilitator of state law, while village customary institutions functioned as guardians of local norms and values ??in society. This collaboration is considered effective in accelerating the case resolution process, reducing the potential for further conflict, and reconstructing social harmony in the village community. However, this study also found a number of obstacles, including differences in perception between formal and customary law, as well as limited human resources and supporting facilities. Based on these findings, it is recommended to strengthen institutional capacity and formulate an integrated mediation mechanism based on the principles of positive law and local culture. Keywords: Collaboration, Bhabinkamtibmas, Customary Institutions, Violence Against Children, mediation, Desa Karamabura Dompu